KAJIAN LITERATUR: KECENDERUNGAN PENGGUNAAN METODOLOGI PENELITIAN DALAM ARTIKEL ILMIAH TERKAIT KURIKULUM MERDEKA DI SD - Pani Suswari; Rifky Aditya Ramadhan; Rika Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A research method is a method used by researchers to obtain research data for specific purposes. The purpose of this study is to examine the trends in research methods used by researchers in conducting research related to the Merdeka Curriculum in elementary schools. The research method used in this study is a literature review. The data collection technique used was the researcher searching for and downloading 28 articles related to the Merdeka Curriculum in elementary schools in 2023 and 2024 in SINTA. The data analysis technique was an article analysis sheet. The results of the study indicate that Among the 28 articles published in SINTA 5 through SINTA 2 journals regarding the Merdeka Curriculum, the most frequently employed research method was the qualitative approach, accounting for 17 of the 28 articles. The remaining 11 articles utilized methods such as mixed methods, R&D, literature reviews, and quantitative approaches